PENGANGGURAN, INVESTASI DAN PERTUMBUHAN EKONOMI - Samuel Revaldo Jeverson Siboro; Roma Uli Maria Situmeang, Olive Katrina Joyanka Sihombing, Josua Pane (Jurnal Ekonomi dan Bisnis, 2025)
Unemployment, investment, and the economy are three interrelated aspects that significantly influence a country's economic development, including Indonesia. A high unemployment rate negatively impacts people's purchasing power and economic growth, whereas investment plays a crucial role in job creation and boosting national productivity. Indonesia's economy continues to evolve amid various challenges, including global economic instability, policy changes, and labor market dynamics. Therefore, the government strives to address these issues through fiscal and monetary policies that support investment climate improvement and promote inclusive and sustainable economic growth. This article discusses the relationship between unemployment, investment, and the Indonesian economy, as well as the strategies that can be implemented to achieve economic stability and prosperity for society.